Association between chemerin, omentin-1 and risk of heart failure in the population-based EPIC-Potsdam study. Issue 1 (December 2017) - Menzel, Juliane; di Giuseppe, Romina; Biemann, Ronald; Wittenbecher, Clemens; Aleksandrova, Krasimira; Eichelmann, Fabian; Fritsche, Andreas; Schulze, Matthias; Boeing, Heiner; Isermann, Berend; Weikert, Cornelia
Abstract The adipokines chemerin and omentin-1 have been suggested to influence cardiovascular function. The study aimed to investigate the longitudinal association between chemerin, omentin-1 concentrations and risk of incident heart failure (HF), respectively. We conducted a case-cohort study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam cohort (n = 27548) including a randomly drawn subsample and all incident HF cases during a mean follow-up of 8.2 ± 1.5 years. A total of 212 incident HF cases and 2168 individuals free of HF cases were included in the study. After multivariable adjustment for established cardiovascular risk factors chemerin was strongly associated with risk of HF (HR per doubling chemerin: 4.91; 95%-CI: 2.57–9.39; p < 0.0001). Omentin-1 was not significantly related to HF risk in the overall study population. However, the association between omentin-1 and HF risk was modified by prevalent coronary heart disease (CHD), showing that the shape of the association was linear in participants without prevalent CHD (HR doubling omentin-1: 2.11; 95%-CI: 1.36–3.27; p linear = 0.0009) and U-shaped in participants with pre-existing CHD (p non-linear = 0.006). Our study provides first evidence for a strong positive association between chemerin and risk of HF. The association between the adipokine omentin-1 and risk of HF may differ according to pre-existing CHD.